Rohingya: a Neglected Ethnic, Potential for Nation Development in Myanmar - Pazli; Feza Pardhana; Rahmat Kurniawan (Jurnal Multidisiplin Madani, 2023)
There has been discrimination against the human rights of the Rohingya ethnic minority in Myanmar. There have been a number of attempts by the incumbent regime to remove their citizenship status in Myanmar. The world community; caring countries; non-state and other international organizations that are pro-humanity reacted strongly. However, the regime in power did not ignore it, even closed itself off from various responses from various parties and still did not recognize the citizenship status of the Rohingya ethnicity. The question is, why does the ruling regime insist on not recognizing the citizenship status of the Rohingya? Why do regional and international organizations respond to discrimination against the Rohingya?; What ideas are offered to make “ethnicity” a capital for nation building?. The research uses qualitative methods with literature study, sourced from secondary data from documentation and literature. The finding is that the Rohingya ethnic citizenship status that is not recognized can perpetuate the domination of the military regime's power in Myanmar. The international response to discrimination in Myanmar is a form of concern for ensuring the upholding of the pillars of democracy, global security, international law and human rights in Myanmar. A new ideology is needed for tomorrow's generation in order to change the "ethnic faction" into the nation's "development energy"